Vita ed essere. Il doppio inizio della Seinsfrage heideggeriana - Mazzarella, Eugenio (Bollettino Filosofico, 2020)
Heidegger has always stated that the distinctive feature of his ontology is the question of Being. But actually, the question with which Heidegger faces philosophy is by no means addressed to Being. It is addressed to “life”, i.e. to the connection, in life, of existence and history as a “living spirit”. It is this question that holds back the mature question on the being from resolving itself in a pure speculative scholasticism on Being and its history. It is this question that fecundates with the question of being the philosophically important nucleus: existential analytics; dialogue with poetry and the work of art; the great question about technique. In the thought that looks into Being in its character as an event, the theme that remains alive is that Being for us is ultimately the world we inhabit. Keywords: Being, Existence, Historicity, Life, Ontology